(3GdCShGb hGdeDSSGJ GdeGdjIs - (3GdRYHj(B, (3eQhGf eMeOs; (3SYjO GdNWjH, CdGAs ((3YeGfs (3OGQ GdeSjQI ddfTQ h GdJhRjY h GdWHGYIs, 2022)
(3jeKd gPG GdcJGH eQLYkG TGedkG heJLOOkG aj eLGd GdeGdjI, MjK jLeY Hjf GdfXQjGJ GdCcGOjejI hGdJWHjbGJ GdYedjI HHQGYI(B. (3jJejR GdcJGH HJbOje eMJhi Zfj heJfhY, jZWj LhGfH eJYOOI ef Yde GdeGdjI, HOkAG ef GdeaGgje GdCSGSjI hUhdkG Edi GdJMdjdGJ GdeYbOI(B.(3CHQR eG jejR gPG GdcJGH(B: (3GdJhGRf Hjf GdCcGOjejI hGdJWHjb(B: (3jLeY GdcJGH Hjf GdTQM GdfXQj ddeaGgje GdeGdjI hHjf CeKdI hMGdGJ YedjI eSJbGI ef GdhGbY, eeG jSgd Ydi GdbGQF age hGSJjYGH gPg GdeaGgje hJWHjbgG aj MjGJg GdYedjI(B. (3GdJQcjR Ydi GdeJYde(B: (3Je JUeje GdcJGH HWQjbI JLYdg efGSHkG dLejY GdaFGJ, HOkAG ef GdWdGH GdLGeYjjf hGdHGMKjf hUhdkG Edi GdeeGQSjf aj eLGd GdeGd hGdCYeGd, MjK jbOe COhGJ hCSFdI JSGYO Ydi JYejb Gdage hJfejI GdegGQGJ GdJMdjdjI(B. (3GdGSJaGOI ef NHQGJ hGSYI(B: (3jSJfO GdcJGH Edi NHQGJ hGSYI ddeDdajf aj eNJda GdeLGdGJ GdCcGOjejI hGdJOQjHjI hGdegfjI, eeG jVef ObI GdeYdheGJ hTehdjJgG(B. (3eGOI YdejI hKbGajI(B: (3jbOe GdcJGH eGOI YdejI eJNUUI aj eLGd GdeGdjI, haj GdhbJ faSg jTHY aVhd GdbGQF hjQaY ef KbGaJg GdeGdjI(B. (3HGNJUGQ, gPG GdcJGH gh Odjd TGed dcd ef jQZH aj JhSjY eOGQcg aj eLGd GdeGdjI, ShGA cGf WGdkHG jHMK Yf eQLY CcGOjej eJejR, Ch eMJQkaG jSYi dJWhjQ egGQGJg, Ch TNkUG egJkeG HRjGOI KbGaJg GdeGdjI(B.s
Keywords: (3GdCShGb GdeGdjIs